A Study on The Perception of Community on The Role of Religion In Character Education For The Young Generation - Setianingsih, Nita; Priyanto, Aris (Averroes: Journal for Science and Religious Studies, 2025)
Background Study: This study is grounded in the increasing moral challenges faced by young people in the era of Artificial Intelligence (AI), where technological advancement and rapid information flow significantly influence behaviors, mindset, and character development. Religious education is considered a fundamental pillar for shaping morality, strengthening ethical awareness, and embedding spiritual values essential for navigating social change. However, its effectiveness in character formation depends greatly on community perceptions and support. This research aims to analyze the role of religious education in the character development of young people amid AI-driven societal transformation, using a field-based study in Randugunting, Bantarbolang Village. Methods: A qualitative method was employed through in-depth interviews, participatory observation, and documentation, with data analyzed using the Miles & Huberman model—data reduction, display, and conclusion drawing. Key Findings: The community generally holds a positive perception of religious education as a source of moral guidance for adolescents, although challenges remain, including economic limitations and low parental educational background. Contributes: empirically to the discourse on religious education in the digital era and offers strategic recommendations for strengthening character education rooted in religious values. Conclusion: affirms that religious education remains relevant and impactful in shaping youth character when supported collaboratively by families, communities, and educational institutions.